PENINGGALAN-PENINGGALAN SEJARAH ISLAM DI ISTANA MAIMUN - Hesty Angraini; Sahli Rahma; Sakina Bela Aqriani; Rosinta Marito Pardosi; Ika Purnamasari (STKIP Subang, 2025)
This study aims to examine the Islamic historical heritage found in Istana Maimun and its relation to the development of Islamic civilization in Medan City during the late 19th century. The research employs a qualitative method using direct observation and documentation of artifacts, architectural elements, and ongoing traditions within the palace environment.The results indicate that Istana Maimun, built during the reign of Sultan Ma'mun Al Rasyid Perkasa Alamsyah, represents the grandeur of the Deli Sultanate and embodies strong Islamic values. This is reflected in its architectural features, such as domes, geometric ornaments, and Arabic calligraphy. In addition, various artifacts—including the royal throne, traditional attire, and ceremonial equipment—demonstrate the integration of Malay culture with Islamic teachings. Furthermore, the findings reveal a close relationship between the palace and the religious life of the community, as seen in Islamic traditions and its proximity to the Al-Mashun Grand Mosque. Therefore, Istana Maimun serves not only as a historical monument but also as a center for preserving Islamic culture and civilization in North Sumatra.